Policy Makers', NGO, and Healthcare Workers' Accounts of Migrants' and Refugees' Healthcare Access Across Europe—Human Rights and Citizenship Based Claims - Bradby, Hannah; Lebano, Adele; Hamed, Sarah; Gil-Salmerón, Alejandro; Durá-Ferrandis, Estrella; Garcés-Ferrer, Jorge; Sherlaw, William; Christova, Iva; Karnaki, Pania; Zota, Dina; Riza, Elena (Frontiers in Sociology, 2020)
Freely available healthcare, universally accessible to the population of citizens, is a key ideal for European welfare systems. As labour migration of the twentieth century gave way to the globalised streams of the twenty-first century, new challenges to fulfilling these ideals have emerged. The principle of freedom of movement, together with large-scale forced migration have led to large scale movements of people, making new demands on European healthcare systems which had previously been largely focused on meeting sedentary local populations’ needs. Drawing on interviews with service providers working for NGOs and public healthcare systems and with policy makers across ten European countries, this paper considers how forced migrants’ healthcare needs are addressed by national health systems, with factors hindering access at organisational and individual level in particular focus. The ways in which refugees’ and migrants’ healthcare access is prevented are considered in terms of claims based on citizenship and on the human right to health and healthcare. Where claims based on citizenship are denied and there is no means of asserting the human right to health, migrants are caught in a new form of inequality.